Philosophy of Science in a Critical Perspective on Modern - Alfariza, Syafira Alvina; Rusdiana, Ike; Suratno, Suratno; Mahardika, I Ketut (International Journal of Education, Information Technology, and Others, 2024)
Science undergoes major changes from time to time. The positive result of this development related to the purpose of knowledge acquisition is that humans become more proficient in fulfilling all their needs. Although it has positive aspects, the development of science also has negative aspects for human life, namely negative elements related to human morality and mentality that are increasingly evident as a result of the difficulty of humans understanding science and technology. The purpose of this research is to better understand the process of science philosophy in the development of current understanding, which is carried out using the SLR (Systematic Literature Review) method. The review of information sources was taken from the Google Scholar database. for Indonesian journals published between 2021 and 2024. The findings of this research are that the role of philosophy in the development of knowledge is recognized as follows: (1) as a source of criticism and reflection on values and morals (moral-axiological), (2) as a source of knowledge, (3) as a source of expanded knowledge, and (4) as a source of knowledge improvement.